2020
DOI: 10.21053/ceo.2019.01830
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of the Modified Epley Maneuver With a Pillow Under the Shoulders

Abstract: Objectives. Canalolithiasis of the posterior semicircular canal (PC) is the most common reason for benign paroxysmal positional vertigo (BPPV). If a patient is diagnosed with PC-BPPV through the Dix-Hallpike test, the modified Epley maneuver (mEpley) is used as the gold standard treatment. To reduce the discomfort of the standard mEpley, we proposed placing a pillow under the shoulders during this therapeutic maneuver. The purpose of this study was to determine whether the therapeutic efficacy of the mEpley wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The EM requires the supine patient’s head and trunk to be rotated after being tilted backward into a slightly head-hanging position with a pillow under the patient’s shoulder to reduce the discomfort . The success rate can be improved by repeating the maneuver 2 to 3 times in 1 session …”
Section: Introductionmentioning
confidence: 99%
“…The EM requires the supine patient’s head and trunk to be rotated after being tilted backward into a slightly head-hanging position with a pillow under the patient’s shoulder to reduce the discomfort . The success rate can be improved by repeating the maneuver 2 to 3 times in 1 session …”
Section: Introductionmentioning
confidence: 99%
“…Recently, some authors reported that a modified version of the DHT with a pillow under the shoulders to resolve patients’ discomfort during the standard DHT had the same diagnostic effectiveness as the standard DHT [ 5 ]. Following the previous report, the authors reported that the therapeutic efficacy of the modified Epley maneuver with a pillow under the shoulders was also comparable to that of the standard modified Epley maneuver [ 6 ]. The authors also stated that this modified method can be helpful for patients who have anxiety about the head-hanging position during treatment and can reduce both the force needed and the physical burden on clinicians because they no longer need to hold onto the patient’s head.…”
mentioning
confidence: 89%
“…However, the study of Lee et al [6] had some limitations: (1) no evaluation of patients' subjective discomfort, (2) a relatively small population, and (3) a short-term follow-up period. In addition, if the size of the pillow is not chosen depending on the size of the patient's body, the patient may not be positioned properly for treatment.…”
mentioning
confidence: 99%
“…BPPV is a common peripheral vestibular disorder whose prevalence is predicted to be approximately 2.4% [ 12 ]. The pathophysiology of BPPV has been attributed to otoconia dislocated from otolith organs, which perturb the endolymphatic flow in the semicircular canals according to head position [ 13 , 14 ]. Therefore, inner ear dysfunctions, for instance, the disturbance of endolymphatic homeostasis or degenerative insults of otoconia, can induce BPPV.…”
Section: Introductionmentioning
confidence: 99%